Supply chain attacks - Quliyev, Rauf; Quluzadə, Rahid; Babayev, Riyad (My University, 2024)
This dissertation is about supply chain attacks.
Keywords: Five ways to minimize risk; Targeted cyber attacks are an advanced persistent threat; SolarWinds incident; Zero Trust; Risk assessment and management; Collaboration and information sharing